2010
DOI: 10.3113/fai.2010.0492
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Arthrodesis Using Anatomically Contoured Anterior Plate

Abstract: The application of an anatomically contoured plate provides many advantages, including less soft tissue disruption by using a single anterior incision, ease of deformity correction, early rehabilitation, and high rate of union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 18 publications
0
45
0
2
Order By: Relevance
“…intertarsal fusion, [1][2][3] total ankle arthroplasty, 4,5 and a combination of these techniques. Ankle arthrodesis is superior to ankle arthroplasty and regarded as the gold standard, with a union rate of 85 to 100%.…”
mentioning
confidence: 99%
“…intertarsal fusion, [1][2][3] total ankle arthroplasty, 4,5 and a combination of these techniques. Ankle arthrodesis is superior to ankle arthroplasty and regarded as the gold standard, with a union rate of 85 to 100%.…”
mentioning
confidence: 99%
“…However, other screw orientations are possible, including the parallel screw technique, which has been reported to result in fusion rates of 95% (48). Another option includes the use of anatomically contoured plates, which, in one small case series, obtained a fusion rate of 90% by 15 weeks postoperative (32) and was found to result in a decreased interval to fusion, greater rigidity (49), and lower AOFAS scale scores compared to conventional lag screw fixation (31). Wera and Sontich (50) reported the outcome of ankle arthrodesis using a custom blade plate, with a 100% fusion rate at 37 months and an average interval to fusion of 3.9 months.…”
Section: Joint Sacrificing Surgerymentioning
confidence: 94%
“…Ankle arthrodesis remains the reference standard for the treatment of pain and deformity secondary to post-traumatic arthritis and for previous infection, osteochondral defects, osteonecrosis of the talus, idiopathic OA, and inflammatory arthropathy, including rheumatoid arthritis (3). Arthrodesis can achieve successful union rates and patient satisfaction outcomes (31)(32)(33)(34). Arthrodesis can also be used as a salvage procedure, both after nonunion of a previous arthrodesis (35) or as revision of total ankle arthroplasty, either with (36,37) or without (38) supplementary fixation adjuncts such as trabecular metal or cage fixation devices.…”
Section: Joint Sacrificing Surgerymentioning
confidence: 99%
“…1 Since 1879, when this surgical procedure was described for the first time, 2 more than 40 different surgical techniques have been described and proven in clinical studies. 3,4 In most patients with ankle arthrodesis, good early relief of pain can be achieved. 3,5 However, many long-term clinical studies have shown that later results of ankle arthrodesis often include premature deterioration of adjacent joints.…”
Section: Historical Perspectivementioning
confidence: 99%